RUSSIAN-AMERICAN RELATIONS IN DONALD TRUMP’S SECOND TERM: BETWEEN DESIRES AND REALITY - Proroković, Dušan (The Policy of National Security, 2026)
Donald Trump’s initiative to restore Russian-American relations by resolving the Ukrainian crisis with partial respect for Russia’s demands seemed surprising and was described as a kind of U-turn in American foreign policy. However, the question is not only what effect such U-turns in bilateral and/or international relations can have, but also whether they can be carried out without major consequences. On the one hand, the Ukrainian crisis is complex; it decisively determines continental security, and therefore, European countries are interested in resolving it. On the other hand, after four years of confrontation, trust between Russia and the collective West has been destroyed, and time is needed to restore it. This research examines the reasons and scope of Donald Trump’s initiative. There is a big difference between the publicly proclaimed desire to contribute to establishing peace and improving Russian-American relations and the realities that arise from the establishment of a balance of power through confrontation. The paper consists of five parts. The introductory section explains the theoretical and methodological frameworks, presents the research question and hypothesis, and defines the concept of “controlled confrontation”. The second part describes the process by which an absolute breach of trust between Russia and the USA led to an escalation of the confrontation. The third part examines changes in the Russian Foreign Policy Concept, and the fourth part examines how the growth of distrust and changes in doctrinal documents contributed to the misunderstanding. The last part is the concluding remarks.